Performance of maize hybrids submitted to different row spacing and population densities - Demétrio, Claudia Sousa; Filho, Domingos Fornasieri; Cazetta, Jairo Osvaldo; Cazetta, Disnei Amélio (Pesquisa Agropecuaria Brasileira, 2009)
The objective of this work was to evaluate the influence of row spacing and population densities on yield and yield components of two maize (Zea mays) hybrids. The experiment was carried out in the agricultural year 2006/2007, in a Typical Haplustox, in a clay texture soil, in Jaboticabal, SP, Brazil. The experimental design was a randomized complete block, with split-split plot with 24 treatments. The main plots were three row spacings (0.40, 0.60 and 0.80 m), the split-plots were two hybrids, and the split-split plots were four population densities (30,000, 50,000, 70,000 and 90,000 plants per hectare). The following variables were evaluated: plant height, first ear height, stem diameter, number of grains (kernels) per ear, mass of 1,000 grains, grain yield and harvest index. Maize grain yield increased with the reduction of row spacing for the evaluated hybrids. The increase of maize populational density resulted in increases of plant and first ear heights and in decrease of the number of grains per ear. The best planting arrangement for both hybrids was 0.40 m row spacing and 75,000 and 80,000 plants per hectare.